2013
DOI: 10.1016/j.jenvman.2013.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Passive remediation of coalbed natural gas co-produced water using zeolite

Abstract: Abstract:Coalbed natural gas (CBNG) co-produced waters can contain sodium (Na þ ) concentrations that may be environmentally detrimental if discharged to receiving bodies of water or applied to land surfaces. A field demonstration and companion laboratory studies were conducted to evaluate the use of a Bear River zeolite (BR-zeolite) for mitigating impacts associated with Na þ in CBNG waters. Bench-scale kinetic and adsorption isotherm studies were performed to determine both the rate and extent of sodium Na þ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The adsorption was also examined in a field site to evaluate the usefulness of zeolites. This test reported that treated PW lowered the damage caused to the soil by Na + ions [120] . In the toluene study, the investigation was conducted in a column and batch experiments.…”
Section: Commercial Adsorbentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption was also examined in a field site to evaluate the usefulness of zeolites. This test reported that treated PW lowered the damage caused to the soil by Na + ions [120] . In the toluene study, the investigation was conducted in a column and batch experiments.…”
Section: Commercial Adsorbentsmentioning
confidence: 99%
“…Non-natural adsorbents such as the commercially available ones were also investigated for the treatment of PW. Belbase et al [120] and Ma et al [121] used zeolite as an adsorbent for the removal of sodium cation (Na + ) and toluene respectively. For the Na + study, PW from coalbed natural showed that Na + adsorption was dependent on the zeolite size.…”
Section: Commercial Adsorbentsmentioning
confidence: 99%
“…Zeolite was used to manufacture ion exchange resin/sorbent to remove cations and anions present in water (Jiménez et al 2018). Studies showed that natural or modified zeolite was able to remove hardness and sodium in produced water (Belbase et al 2013;Zhao et al 2008Zhao et al , 2009. However, major applications of zeolite in produced water treatment focus on the removal of organic components such as benzene, toluene, ethylbenzene, and xylenes (BTEX) compounds (Ranck et al 2005).…”
Section: Removal Of Inorganic Ions Toc and Tssmentioning
confidence: 99%
“…Zero-valentiron (ZVI) was the first and mainly used in PRB as the reactive material for converting contaminants to nontoxic or immobile species, dehalogenating hydrocarbon sand precipitating anions and oxyanions for grounder water remediation, (United States Environmental Protection Agency, 1998;Scherer et al, 2000;Tratnyek et al, 2003;Gillham et al, 2010); Microorganisms or the material which stimulates the growth of microbes, such as humic materials and oxides, were commonly proposed as biological materials for PRB to remediate the nitrate and sulfate species (United States Environmental Protection Agency, 1998;Scherer et al, 2000);Zeolite was another ideal alternative material for PRB based on its adsorption capacity and high ion exchange capacities (Jorgensen and Weatherley, 2003;Altare et al, 2007;Fronczyk, 2008;Belbase et al, 2013;Joanna et al, 2013).…”
Section: Introductionmentioning
confidence: 99%